Sparganosis of a thoracic vertebra misdiagnosed as bone metastasis from lung cancer - Meng, Yiming; Wan, Wen; Xiong, Zhi-Chao; Wu, Ping; Zhang, Ning; Yu, Yan-Qing; Huang, Shan-Hu; Liu, Zhi-Li; Liu, Jia-Ming (International journal of infectious diseases, 2023)
•A rare case of thoracic vertebral sparganosis was diagnosed.•Vertebral lesion resection and praziquantel treatment were given to this patient.•Serum antibody tests are useful for the diagnosis of sparganosis. Sparganosis is a rare parasitic infection caused by plerocercoid tapeworm larvae. We described a case of a 27-year-old man presenting with numbness in both legs and masses in the right lung and spine, initially thought to have spinal metastasis from lung cancer. However, after pathological and parasitological examinations, the patient was found to have spinal sparganosis, likely due to a history of consuming raw frogs. The patient was successfully treated with praziquantel, resulting in the recovery of muscle strength in his legs. This case highlights the importance of considering spinal sparganosis as a differential diagnosis in patients with spinal masses, especially those with a history of consuming raw or undercooked frogs. Accurate diagnosis and early treatment are crucial for managing this infection.